City Production through Sexuality and Space Appropriationas Perspective: A Case Study at Sao Pauloas Gay Street (Global Journal of Human-Social Science, 2013)
Which identities a space can acquire What about a public space For instance a street how can it be defined and who is able to do so A street can acquire a sexual identity This article concentrates on some aspects observed in my master s dissertation My research was ethnographic based and captures the appropriation of public spaces in large cities as a way of defining a socio-sexual identity in this case FreiCaneca Street in Sao Paulo In this article I will address some of the data from my participant observation which tells how the identity s definitions are constructed at street s space and at the spaces on the street I also tackle how these settings interact with everyday local basis make possible the separation into groups and trigger political demonstrations Moreover I address how these definitions help to outline the city of S o Paulo and shift their centralities
Keywords: urban sociology; ethnographic research; sexualities; urban planning; sE3; o paulo city